Antimodified protein antibody response pattern influences the risk for disease relapse in patients with rheumatoid arthritis tapering disease modifying antirheumatic drugs. Issue 2 (20th June 2016) - Figueiredo, Camille P; Bang, Holger; Cobra, Jayme Fogagnolo; Englbrecht, Matthias; Hueber, Axel J; Haschka, Judith; Manger, Bernhard; Kleyer, Arnd; Reiser, Michaela; Finzel, Stephanie; Tony, Hans-Peter; Kleinert, Stefan; et al.
Abstract : Objective: To perform a detailed analysis of the autoantibody response against post-translationally modified proteins in patients with rheumatoid arthritis (RA) in sustained remission and to explore whether its composition influences the risk for disease relapse when tapering disease modifying antirheumatic drug (DMARD) therapy. Methods: Immune responses against 10 citrullinated, homocitrullinated/carbamylated and acetylated peptides, as well as unmodified vimentin (control) and cyclic citrullinated peptide 2 (CCP2) were tested in baseline serum samples from 94 patients of the RETRO study. Patients were classified according to the number of autoantibody reactivities (0–1/10, 2–5/10 and >5/10) or specificity groups (citrullination, carbamylation and acetylation; 0–3) and tested for their risk to develop relapses after DMARD tapering. Demographic and disease-specific parameters were included in multivariate logistic regression analysis for defining the role of autoantibodies in predicting relapse. Results: Patients varied in their antimodified protein antibody response with the extremes from recognition of no (0/10) to all antigens (10/10). Antibodies against citrullinated vimentin (51%), acetylated ornithine (46%) and acetylated lysine (37%) were the most frequently observed subspecificities. Relapse risk significantly (p=0.011) increased from 18% (0–1/10 reactivities) to 34% (2–5/10) and 55% (>5/10). With respect to specificity groups (0–3), relapse risk significantly (p=0.021) increased from 18% (no reactivity) to 28%, 36% and finally to 52% with one, two or three antibody specificity groups, respectively. Conclusions: The data suggest that the pattern of antimodified protein antibody response determines the risk of disease relapse in patients with RA tapering DMARD therapy. Trial registration number: 2009-015740-42; Results.